The professed effect of stigma on community psychiatric nurses in the Greater Accra region of Ghana - Abigail Ansere Buertey (BMC Psychiatry, 2022)
Abstract Background Stigma is a major factor that inhibits Mental Health Nurses work, especially Community Psychiatric Nurses, in terms of productivity. Even though mental health services have improved drastically, because of decentralization of mental health care, a lot more people still have reservations when it comes to mental health nurses particularly Community Psychiatric Nurses. The purpose of the study was to explore the professed effects of stigma on CPNs in the Southern part of Ghana. Methods The study was carried out in three district hospitals (Ga South, Ga Central and Okaikoi) all in the Accra Metropolis. The aim of the study was to describe how stigma affects Community Psychiatric Nurses. A qualitative descriptive exploratory design was adopted for the study. The purposive sampling technique was used to recruit participants. Data was saturated with 12 participants, aged between 25 and 40 years. The audio-taped interviews were transcribed verbatim and afterwards analyzed using thematic and content analysis. Results The findings gathered from participants revealed that Community Psychiatric Nurses experienced various effects of stigma, such as low productivity, depression, and anger. Most of the participants recounted how stigmatization had affected their work both in the hospital setting and in their communities. Conclusion The study showed that Community Psychiatric Nurses carried out their activities with much difficulty, because of their poor image. They stressed the need for recognition and support from employers, stakeholders and the general community so as to boost confidence and morale with the resultant effect of better healthcare delivery.